Poly Royal 1948 - part 1 (1948)
[00:00:11] Opening shot of speeches on the football field [00:01:52] Poses with the football team and game footage [00:05:33] Baseball Game Footage [00:05:48] Tennis Footage [00:06:48] Livestock judging [00:07:41] Sheep shaving demonstrations [00:08:46] Various shots of various competitions [00:10:17] Various crowd shots [00:12:40] Poly Royal Rodeo [00:14:16] End footage